Muscular glucose metabolism in middle-age trained rats - Ghezzi, Ana Carolina [UNESP]; Cambri, Lucieli Teresa [UNESP]; Botezelli, José Diego [UNESP]; de Mello, Maria Alice Rostom [UNESP] (Springer Nature, 2017)
Aging decreases the normal organism physiological functions. On the other hand, physical exercise shows health benefits, but little information is known about physical deconditioning at aging. The aim of the present study was to analyze the glucose muscle metabolism in middle-age Wistar rats in response to conditioning and physical deconditioning. The study included three groups: Control (C)—not performed physical training; Trained (T)—performed physical training from 4 to 12 months—swimming exercise for 1 h per day, 5 days per week at 80% of maximal lactate stead state—MLSS; Detrained (D)—performed to physical training from 4 to 8 months and assessed at 12 months (D). Physical training at submaximal intensities induced decreases in body weight (C 588 ± 71, T 515 ± 72, D 576 ± 62 g), and the weight of mesenteric adipose tissue (C 4399 ± 643, T 3007 ± 811, D 4085 ± 540 mg/g), and increases in exercise workload in MLSS intensity (C 4.6 ± 0.4, T 5.8 ± 1.3, D 5.3 ± 0.4% body weight), glucose tolerance (C 12314 ± 1122, T 8428 ± 853, D 9433 ± 1200 mg/dL 120 min), glycogen deposits (C 0.48 ± 0.07, T 0.66 ± 0.18, D 0.46 ± 0.10 mg/100 mg) and glucose uptake by skeletal muscle (C 1.96 ± 0.54, T 3.28 ± 0.53, D 2.55 ± 0.35 μmol/g/h) in trained animals. Additionally, the improvement in exercise load in MLSS, glucose tolerance and glucose uptake was maintained after physical detraining. In summary, the physical training promotes alterations in body weight, fat tissue, aerobic capacity and muscular glucose metabolism in middle-age rats. However, only the aerobic capacity and muscular glucose metabolism were maintained after detraining.
Keywords: Aging; Glucose uptake; Glycogen; Maximal lactate steady state (MLSS); Physical exercise